The Lysine Residues within the Human Ribosomal Protein S17 Sequence Naturally Inserted into the Viral Nonstructural Protein of a Unique Strain of Hepatitis E Virus Are Important for Enhanced Virus Replication - Kenney, Scott P. (J Virol, 2015)
Hepatitis E virus (HEV) is an important but extremely understudied human pathogen. Due largely to the lack of an efficient cell culture system for HEV, the molecular mechanisms of HEV replication and pathogenesis are poorly understood. Recently, a unique genotype 3 strain of HEV recovered from a chronically infected patient was adapted for growth in HepG2C3A human hepatoma cells. The adaptation of the Kernow C-1 P6 HEV to propagate in HepG2C3A cells selected for a rare virus recombinant that contains an insertion of a 171-nucleotide sequence encoding amino acids 21 to 76 of the human ribosomal protein S17 (RPS17) within the hypervariable region (HVR) of the HEV ORF1 protein. When the RPS17 insertion was placed into a strain of genotype 1 HEV which infects only humans, it expanded the host range of the virus, allowing it to infect cell lines from multiple animal species, including cow, dog, cat, chicken, and hamster. In this study, we utilized forward and reverse genetics to attempt to define which aspects of the RPS17 insertion allow for the ability of the Kernow C-1 P6 HEV to adapt in cell culture and allow for expanded host tropism. We demonstrate that the RPS17 sequence insertion in HEV bestows novel nuclear/nucleolar trafficking capabilities to the ORF1 protein of Kernow P6 HEV and that lysine residues within the RPS17 insertion, but not nuclear localization of the ORF1 protein, correlate with the enhanced replication of the HEV Kernow C-1 P6 strain. The results from this study have important implications for understanding the mechanism of cross-species infection and replication of HEV. IMPORTANCE HEV is an important pathogen worldwide. The virus causes high mortality (up to 30%) in pregnant women and has been recognized to cause chronic hepatitis in immunocompromised populations. The life cycle of HEV has been understudied due to a lack of sufficient cell culture systems in which to propagate the virus. Recently, insertions and rearrangements of the hypervariable region (HVR) within the HEV genome, allowing for cell culture adaptation and expansion of the host range, have been reported. We utilized these cell culture-adapted HEV strains to assess how the HVR may be involved in virus replication and host range. We provide evidence that insertion of the RPS17 sequence in HEV likely confers nuclear trafficking capabilities to the nonstructural protein of the virus and that lysine residues within the RPS17 insertion are important for enhanced replication of the virus. These data will help to elucidate the mechanism of cross-species infection of HEV in the future.